Several Problematic Words in the Turkish Mirajname Text Found in the Kitab of Ivan Lutskevich - Durgut, Hüseyin (Slavistica Vilnensis, 2016)
Kitab manuscripts are one of the most important parts of the surviving fund of manuscripts of Lithuanian Tatars. Lithuanian Tatars lost their mother tongue for various reasons in 16th–17th centuries, but have preserved their faith and Tatar identity until nowadays. Languages, spoken by ethnic groups living alongside Tatars, replaced the Tatar language. Lithuanian Tatars felt the need for translations in order to fulfill their religious needs. This gave birth to the tradition of Lithuanian Tatar manuscripts, written in Slavic languages using Arabic script. These Arabo-graphic manuscripts preserved texts concerning such languages as Arabic, Chagatai Turkic, old Turkey Turkish, Belarussian and Polish. In this study, several problematic words in the Turkish text of Miracname found in the Kitab of Ivan Lutskevich, were analysed. The author tried to compare these faulty words with their equivalents in Mirajname texts written in old Turkey Turkish and to show their correct versions.